2009
DOI: 10.1111/j.1365-2966.2009.13759.x
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent destruction of clouds - I. Ak-ε treatment of turbulence in 2D models of adiabatic shock-cloud interactions

Abstract: The interaction of a shock with a cloud has been extensively studied in the literature, where the effects of magnetic fields, radiative cooling and thermal conduction have been considered. In many cases, the formation of fully developed turbulence has been prevented by the artificial viscosity inherent in hydrodynamical simulations. This problem is particularly severe in some recent simulations designed to investigate the interaction of a flow with multiple clouds, where the resolution of individual clouds is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(171 citation statements)
references
References 88 publications
7
162
1
1
Order By: Relevance
“…5 presents snapshots of the time evolution of the density distribution for simulation m10c1b1l4o45pa. The evolution of the filament broadly follows the stages outlined in section 4.1 of Pittard et al (2009). First, the filament is struck and compressed by the shock front, and a bow shock is formed.…”
Section: Filament Morphologymentioning
confidence: 96%
See 2 more Smart Citations
“…5 presents snapshots of the time evolution of the density distribution for simulation m10c1b1l4o45pa. The evolution of the filament broadly follows the stages outlined in section 4.1 of Pittard et al (2009). First, the filament is struck and compressed by the shock front, and a bow shock is formed.…”
Section: Filament Morphologymentioning
confidence: 96%
“…We are therefore able to vary the aspect ratio and orientation of the filament in order to investigate how such a change might alter the interaction. The filament has been given smooth edges over about 10 per cent of its radius, using the density profile from Pittard et al (2009), with p 1 = 10 giving a reasonably sharp-edged cloud. The filament and surrounding ambient medium are in pressure equilibrium.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of magnetized clouds (Orlando et al 2008), shocked clouds with considerable particle acceleration would fall in-between the limit of completely suppressed thermal conduction (HY runs) and the unmagnetized limit of conduction (RC runs) discussed in this paper. Pittard et al (2009) demonstrated that turbulence plays an important role in shock-cloud interactions, and that environmental turbulence adds a new dimension to the parameter space. In particular, these authors showed that turbulence is generated mainly around the cloud boundary and in the cloud wake after ∼τ cc , the main effect being that clouds subject to a highly turbulent post-shock environment are destroyed significantly more rapidly than those within a smooth flow: the greater the cloud density contrast χ, the higher the effect of turbulence (for instance, for χ ≈ 100, the effect of the post-shock turbulence dominates the shock-cloud interaction).…”
Section: Limits Of the Modelmentioning
confidence: 99%
“…In particular, these authors showed that turbulence is generated mainly around the cloud boundary and in the cloud wake after ∼τ cc , the main effect being that clouds subject to a highly turbulent post-shock environment are destroyed significantly more rapidly than those within a smooth flow: the greater the cloud density contrast χ, the higher the effect of turbulence (for instance, for χ ≈ 100, the effect of the post-shock turbulence dominates the shock-cloud interaction). On the other hand, an efficient thermal conduction smooths the cloud boundary very quickly (see Paper I), and turbulence grows more slowly around clouds with a smooth density profile (Pittard et al 2009). Thus we are confident that our results are valid and the diagnostics proposed here can be applied to clouds of moderate density contrast (i.e., the effects of turbulence poorly influence the shockcloud interaction at early evolutionary stages for t < τ cc ) and smooth density profiles (i.e., the growth of turbulence around clouds is slow), which we have considered here.…”
Section: Limits Of the Modelmentioning
confidence: 99%